Characterize Type of Splicing Languages via Directed Splicing Graph - Nooradelena, Mohd Ruslim; Yuhani, Yusof; Mohd Sham, Mohamad; Mohd Firdaus, Abdul-Wahab; Faisal, Faisal (Semarak Ilmu Publishing, 2025)
A splicing system is a formal characterization of the ability to generate certain enzymatic activities acting on deoxyribonucleic acid (DNA) molecules. In this paper, the results from Laun’s experiment are used in characterizing the type of splicing languages. In the experiments, two initial strings are involved with different features on the selected restriction enzymes. Case I and Case II discussed in this paper show that the splicing languages obtained from these experiments are in adult and limit languages. Nevertheless, the result obtained in this paper is more precise in showing the type of splicing languages which is beyond adult and limit languages when presented via a directed splicing graph. The features of the restriction enzyme that affect the formation of active persistent language are investigated based on the results proposed by Yusof.